THE INFLUENCE OF SOCIAL MEDIA ON THE MENTAL HEALTH OF GENERATION Z AMONG NEW JOHARS - Fazilan Eka Rusnawan; Muhamad Zakin; Naufal Muhadzdzib (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine and analyze the influence of social media usage on the mental health conditions of Generation Z in the Johar Baru area. The research method used is a qualitative approach presenting descriptive data. Data collection was conducted by distributing questionnaires with closed-ended statements online using Google Forms. The population of this study focuses on all Generation Z individuals residing in the Johar Baru district. Data analysis was carried out through a systematic process of organizing and categorizing non-numerical data patterns. The questionnaire results show that massive social media usage exerts a significant impact on the mental health of respondents. The majority of Generation Z in Johar Baru are vulnerable to constantly engaging in social comparison against life standards displayed on digital platforms, while experiencing negative impacts such as insecurity, cyberbullying, anxiety, and the FOMO (fear of missing out) phenomenon. Nevertheless, the research results also indicate that social media can still provide positive impacts in the form of social support, provided it is managed and utilized wisely